2021
DOI: 10.2147/ott.s288442
|View full text |Cite
|
Sign up to set email alerts
|

Banxia Xiexin Decoction Inhibits the Expression of PD-L1 Through Multi-Target and Multi-Pathway Regulation of Major Oncogenes in Gastric Cancer

Abstract: Purpose: Banxia xiexin decoction (BXXX) is a classical Chinese herbal compound for the treatment of gastrointestinal diseases. Its ingredients are also considered helpful for cancer rehabilitation. Here, we will explore the regulatory mechanism of BXXX acting on PD-L1 in gastric cancer (GC). Methods: GC samples and the general baseline data of the patients were collated. Immunohistochemical (IHC) detected the expression of programmed cell death-ligand 1(PD-L1), hypoxia-inducible factor-1 (HIF-1), epidermal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The interaction enables PIK3R1 to the EGFR receptor, enhancing PI3K activity and promoting the phosphorylation of AKT and MMP9. In addition, MMP9 promotes the release of growth factors, thus activating the MAPK and PI3K/AKT pathways that activate MMP9 and MMP13 by regulating the negative feedback [ 41 ]. Activated MMP9 degrades the tumor basement membrane and ECM, thus promoting the formation of blood vessels and migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction enables PIK3R1 to the EGFR receptor, enhancing PI3K activity and promoting the phosphorylation of AKT and MMP9. In addition, MMP9 promotes the release of growth factors, thus activating the MAPK and PI3K/AKT pathways that activate MMP9 and MMP13 by regulating the negative feedback [ 41 ]. Activated MMP9 degrades the tumor basement membrane and ECM, thus promoting the formation of blood vessels and migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through cellular and animal experiments, Xuan Feng et al demonstrated that BXXX exerted antitumor effects by decreasing IL-6/JAK/STAT3-mediated PD-L1 activity and improved drug sensitivity in gastric cancer cells by regulating the expression of 6-O-methylguanine-DNA methyltrans-ferase(MGMT) [ 52] . In another study by Xuan Feng, network tool analysis and experimental validation led to the conclusion that key molecules such as PD-L1, HIF-1, EFGR, IFNGR, and TLR4 in each pathway of the BXXX regulatory network have targeting effects, which was veri ed by cellular and animal experiments, nally con rming the mechanism of BXXX's multi-target and multi-pathway effects on gastric cancer [ 53] . As an ancient formula in Chinese medicine, BXXX is still used for digestive system diseases, but its composition is complex and pharmacological research is still inadequate.…”
Section: Banxia Xiexin Decoctionmentioning
confidence: 92%
“…10 BXD targets the PD-L1, HIF-1, EGFR, and TLR4 pathways, influencing GC cell apoptosis and proliferation. 11 Components, such as β-sitosterol, berberine, coptisine, and ginsenoside, classified based on medicinal flavor, directly or indirectly contribute to gastrointestinal disease management. 12 Network pharmacology, which integrates multiple theories, such as systems biology, proteomics, and genomics, is crucial to understanding TCM action mechanisms through a combination of data analysis, computer simulations, and information retrieval from comprehensive databases.…”
Section: Introductionmentioning
confidence: 99%
“…It significantly improves symptoms of chronic atrophic gastritis and reduces gland atrophy, intestinal metaplasia, and atypical hyperplasia of the gastric mucosa . BXD targets the PD-L1, HIF-1, EGFR, and TLR4 pathways, influencing GC cell apoptosis and proliferation . Components, such as β-sitosterol, berberine, coptisine, and ginsenoside, classified based on medicinal flavor, directly or indirectly contribute to gastrointestinal disease management …”
Section: Introductionmentioning
confidence: 99%